Analyzing Moran’s dimensions of culture in an English conversational course at UCR - Elizondo González, José Fabián (Revista de Lenguas Modernas, 2018)
Understanding the source of cultural differences contributes to effective communication when working across cultures. EFL learners must build intercultural skills not only for improving their communication skills, but also for satisfying their future work demands. This mixed methods research study examines EFL learners as users of English in multicultural environments in a conversational course at the University of Costa Rica. A book analysis, a questionnaire, and an interview were used to collect data about the number and importance of culturerelated activities found in the textbook used, about the instructor and learners’ level of cultural awareness, and about their degree of satisfaction in terms of teaching and learning about culture to determine if the culture-related courseobjectives are being met. The results reflect that Moran’s dimensions of culture are not being explicitly taught, that learners may have difficulties explaining what learning culture is about, and that their overall satisfaction can be rated with a 6 out of 10. The conclusion can also be drawn that the learners’ general dissatisfaction may have to do with the fact they are not exposed to cultural learning outcomes explicitly. Following an analysis of the research results, some recommendations for teaching culture will also be presented.